2009
DOI: 10.1080/17429140903267814
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds from young peach shoots attract males of oriental fruit moth in the field

Abstract: The oriental fruit moth (OFM) is one of the most serious pests of commercial fruit orchards worldwide. Newly planted peach trees in particular, can be very attractive for mated OFM females for oviposition. Samples of airborne host plant volatiles from intact young peach shoot tips and old leaves of the same potted plants were collected and analyzed with a gas chromatograph-mass spectrometer. Chemicals present in young shoot tips, but not in old leaves, were used for field trials. Moth capture by traps with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…A number of laboratory and field studies have evaluated various host plant volatiles for G. molesta and achieved variable results. For example, either β‐ocimene or ( Z )‐3‐hexenyl acetate alone or in various HPV blends was found to increase moth catches (Il’ichev et al., ; Knight et al., ; Natale et al., ; Piñero & Dorn, ), or provided variable results, such as β‐ocimene improved the performance of TAS‐baited traps (Knight et al., ); but pear ester plus β‐ocimene did not improve the 2‐PH lure (Knight, Cichon, et al., ). Similar to this later study, we found that neither β‐ocimene nor ( Z )‐3‐hexenyl acetate affected moth catches when used with either 2‐PH or TA/AA lures, and likely neither volatile will be developed further through our trials.…”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratory and field studies have evaluated various host plant volatiles for G. molesta and achieved variable results. For example, either β‐ocimene or ( Z )‐3‐hexenyl acetate alone or in various HPV blends was found to increase moth catches (Il’ichev et al., ; Knight et al., ; Natale et al., ; Piñero & Dorn, ), or provided variable results, such as β‐ocimene improved the performance of TAS‐baited traps (Knight et al., ); but pear ester plus β‐ocimene did not improve the 2‐PH lure (Knight, Cichon, et al., ). Similar to this later study, we found that neither β‐ocimene nor ( Z )‐3‐hexenyl acetate affected moth catches when used with either 2‐PH or TA/AA lures, and likely neither volatile will be developed further through our trials.…”
Section: Discussionmentioning
confidence: 99%
“…(Hansson et al, 1989) and Heliothis subflexa (Guenée) (Baker et al, 2004) relatively smaller percentages of unresponsive ORNs were reported in sensilla trichodea (11% and 2%, respectively). Male G. molesta respond behaviorally to plant volatiles (Varela et al, 2011a;Il'ichev et al, 2009;Lu et al, 2013), so some of their unresponsive ORNs could be tuned to plant volatiles. In addition, ORNs unresponsive to pheromone compounds could be used to detect pheromone compounds from other species that inhibit male G. molesta response to the female pheromone, such as Z6-12:Ac and Z10-14:OH (Guerin et al, 1986;Tòth et al, 1991), as happens in other species (reviewed in De Bruyne and Baker, 2008).…”
Section: Pheromone-unresponsive Ornsmentioning
confidence: 99%
“…The first field study reporting attractive host plant volatiles for G. molesta found a 1 : 2 : 2 ratio of ( Z )‐3‐hexenyl acetate, ( E )‐ β ‐ocimene and ( E )‐ β ‐farnesene, or either ( E )‐ β ‐ocimene or ( E )‐ β ‐farnesene alone was as attractive as the TAS bait to male but not female G. molesta in Australia (Il'ichev et al. ). The first field study demonstrating a host plant volatile blend attractive to both sexes of G. molesta used six‐ and eight‐component blends derived from Chinese Pear Varieties (Lu et al.…”
Section: Introductionmentioning
confidence: 99%